Catheter Ablation for Atrial Fibrillation: Electrogram-Guided Methods - Orozco-Duque, A.; Morillo, C.; Tobón, C.; Ugarte, J. P.; Bustamante, J. (Revista Mexicana de Ingenieria Biomedica, 2018)
Radiofrequency catheter ablation has evolved into an effective treatment option for drug-resistant patients with atrial fibrillation. Electrical isolation of the pulmonary veins has become the standard ablation strategy mainly in patients with paroxysmal atrial fibrillation. However, the success rate of pulmonary veins isolation is about 50% in patients with persistent atrial fibrillation. Although different strategies to guide the electrophysiologist in ablation procedures have been proposed. Recent studies show that the generation of additional ablation lines guided ana-tomically or by fragmented complex electrograms mapping does not improve the success rate of the conventional pulmonary veins isolation procedure. In this review, we describe the limitations of current electrophysiological mapping methods, the new electrogram evaluation strategies and the signal processing methods that are proposed in the immediate future, to guide ablation procedures, particularly in patients with atrial fibrillation persistent.